Role of Hybrid Brain Imaging in Neuropsychiatric Disorders - Amer M. Burhan; Nicole M. Marlatt; Lena Palaniyappan; Udunna C. Anazodo; Frank S. Prato (Diagnostics, 2015)
This is a focused review of imaging literature to scope the utility of hybrid brain imaging in neuropsychiatric disorders. The review focuses on brain imaging modalities that utilize hybrid (fusion) techniques to characterize abnormal brain molecular signals in combination with structural and functional changes that have been observed in neuropsychiatric disorders. An overview of clinical hybrid brain imaging technologies for human use is followed by a selective review of the literature that conceptualizes the use of these technologies in understanding basic mechanisms of major neuropsychiatric disorders and their therapeutics. Neuronal network abnormalities are highlighted throughout this review to scope the utility of hybrid imaging as a potential biomarker for each disorder.